Surgical and non-surgical management of Dushtavrana: A review - Oza, Bharat Kailash (Journal of Drug Delivery and Therapeutics, 2019)
Vrana (ulcer) is one of the common pathological conditions affecting large number of word wide population from many years. Vrana means discontinuity to the skin due to the some exogenous or endogenous factors including cuts or wound. Ayurveda mentioned that if Vrana not treated properly at initial stage then it turned to non-healing ulcer means Dushtavrana. Vitiation of Doshas & Rakta as a consequence of injury involve in pathogenesis of Dushtavrana. Therefore Doshas & Rakta pacifying approaches recommended to stops pathological progression of Dushtavrana. Considering this fact ayurveda literature also suggested various approaches for the management of Dushtavrana like; herbal drugs, traditional ayurveda formulation, surgical interventions and Shodhna chikitsa, etc. The approaches for the management of Dushtavrana aims decrease production of discharge, relief in granulation, pain and burning sensation due to the antibacterial, anti inflammatory, Vranashodhak and Vranaropak properties of therapy. Present article summarized some important surgical and non-surgical approaches for the management of Dushtavrana in aview to explore this area for future research perspectives.Keywords: Ayurveda, Vrana, Ulcer, Dushtavrana, Surgery.